Nano or Not Nano? A Structured Approach for Identifying Nanomaterials According to the European Commission's Definition. Issue 36 (2nd August 2020) - Mech, Agnieszka; Wohlleben, Wendel; Ghanem, Antoine; Hodoroaba, Vasile‐Dan; Weigel, Stefan; Babick, Frank; Brüngel, Raphael; Friedrich, Christoph M.; Rasmussen, Kirsten; Rauscher, Hubert
Abstract: Identifying nanomaterials (NMs) according to European Union legislation is challenging, as there is an enormous variety of materials, with different physico‐chemical properties. The NanoDefiner Framework and its Decision Support Flow Scheme (DSFS) allow choosing the optimal method to measure the particle size distribution by matching the material properties and the performance of the particular measurement techniques. The DSFS leads to a reliable and economic decision whether a material is an NM or not based on scientific criteria and respecting regulatory requirements. The DSFS starts beyond regulatory requirements by identifying non‐NMs by a proxy approach based on their volume‐specific surface area. In a second step, it identifies NMs. The DSFS is tested on real‐world materials and is implemented in an e‐tool. The DSFS is compared with a decision flowchart of the European Commission's (EC) Joint Research Centre (JRC), which rigorously follows the explicit criteria of the EC NM definition with the focus on identifying NMs, and non‐NMs are identified by exclusion. The two approaches build on the same scientific basis and measurement methods, but start from opposite ends: the JRC Flowchart starts by identifying NMs, whereas the NanoDefiner Framework first identifies non‐NMs. Abstract : The NanoDefiner Framework facilitates regulatory identification of nanomaterials and non‐nanomaterials. Matching material properties and methods' performance to select the optimal measurement method for particle size distribution enables a reliable decision respecting regulatory requirements. This is illustrated by examples and compared with a decision flowchart of the European Commission's (EC's) Joint Research Centre, which rigorously follows the EC nanomaterial definition.